A Puppet No More: A Novella Exploring Self-Esteem Issues in Adolescents - Veronica Febriyanti; Dwi Setiawan (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
The process of maturation for adolescents happens simultaneously and stems from demands from their surroundings. As a result, they are dissatisfied with themselves and develop detrimental practices, such as low self-esteem. This creative work aims to explore the struggles of low self-esteem in adolescents. Specifically, it discusses the symptoms, causes, and solutions. It is written in the form of a novella supported by Carl Rogers’ Theory of Personality Development and Paul Gilbert’s Social Mentality Theory. The protagonist’s low self-esteem is shown through her anxiety, dependency on parental regard, and acts of denial which are caused by the high expectations from her family and social environment. She constantly tries to fulfill these expectations which cause her confidence to deteriorate. Eventually, she learns how to overcome her struggles by coming to terms with herself and learning self-forgiveness. This work falls under the coming-of-age genre as it showcases the protagonist’s process of maturity.